Inventarisation of Protozoan and Arthropoda Ectoparasitic Infestation in Freshwater Fish in Banyuwangi City, East Java - Mohammad Faizal Ulkhaq; Darmawan Setia Budi; Kismiyati , (Journal of Aquaculture Science, 2018)
Detriment caused by ectoparasitic infestation was not as big detriment caused by infestation of other organisms such as viruses and bacteria, but it could be a predisposing factor for the infection of more dangerous pathogenic in fish. The aims of this study was to inventory ectoparasites that infecting freshwater fish cultivated in several districts in the Banyuwangi, in which the results were expected to be used as a reference in an effort to prevent the spread of disease in fish culture. The sample of research consisted of tilapia fish, carp and catfish which were obtained from six sub districts in Banyuwangi, those were Kota, Kabat, Licin, Kalipuro, Giri, and Glagah. The ectoparasite examination method was performed naturally by scraping the surface of the body, fins and gills of the fish, then observed under a microscope with magnification ranging from 40 to 400x. The results of further observations were documented and identified by key identification. Ectoparasites which were found infesting freshwater fish in the city of Banyuwangi consisted of 4 genuses: namely Argulus, Lernaea, Chonopeltis and Trichodina. Further research is needed to determine the prevalence and intensity of ectoparasites in order to prevent the spread of ectoparasites in other regions.   Keywords: Inventarisation, ectoparasites, freshwater fish, Banyuwangi